Buffet hypothesis for microbial nutrition at the rhizosphere - Lopez-Guerrero, Martha; Ormeño-Orrillo, Ernesto; Rosenblueth, Monica; Martinez-Romero, Julio; Martinez-Romero, Esperanza (Frontiers in Plant Science, 2013)
An emphasis is made on the diversity of nutrients that rhizosphere bacteria may encounter derived from roots, soil, decaying organic matter, seeds or the microbial community. This nutrient diversity may be considered analogous to a buffet and is contrasting to the hypothesis of oligotrophy at the rhizosphere. Different rhizosphere bacteria may have preferences for some substrates and this would allow a complex community to be established at the rhizosphere. To profit from diverse nutrients, root associated bacteria should have large degrading capabilities and many transporters (seemingly inducible) that may be encoded in a significant proportion of the large genomes that root associated bacteria have. Rhizosphere microbes may have a tendency to evolve towards generalists. We propose that enzymes encoded by many genes with unknown function may participate in degrading diverse rhizosphere substrates. Knowledge of bacterial genes required for nutrition at the rhizosphere will help to better make use of bacteria as plant-growth promoters in agriculture.